Compliance with the implementation of pre-anesthesia assessment toward the prevention of adverse events in the operating room - Noprianty, Richa; Mutmainah, Ina; Wahdana, Wahyu; Wahyudid, Fikri Mourly (Gaceta Médica de Caracas, 2025)
Introduction: Compliance with the implementation of pre-anesthesia assessment is an essential component of healthcare service quality aimed at preventing and minimizing adverse effects on patients related to anesthesia services and is a key aspect for identifying potential adverse events during and after surgery. Objective: This study aims to determine the relationship between compliance with the implementation of pre-anesthesia assessment and the prevention of adverse events. Method: This study used a quantitative method and analytic design with a cross-sectional approach.